2015
DOI: 10.1257/aer.p20151052
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization and the Skill Premium: A Local Labor Markets Approach

Abstract: Trade economists have long studied the effects of globalization on wage differences between workers with different levels of skill or education.1 This literature has generally sought to link globalization to changes in the economy-wide skill premium. Attanasio et al. (2004) and Gonzaga et al. (2006) are salient examples that investigate whether changes in sector-specific prices or tariffs, changes in skill composition within and across sectors, and movements in the skill premium are consistent with the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 8 publications
3
57
0
Order By: Relevance
“…Table A.2 in Appendix C shows our main results from Tables 3 and 4 with the p-values from our benchmark specification (simple robust standard errors), with clustered standard errors at the meso-region level, and bootstrapped standard errors. Part of the previous literature uses clustered standard errors at the level of aggregation immediately above micro-regions, which in the Brazilian case would correspond to the meso-region (e.g Dix-Carneiro and Kovak, 2015;Dix-Carneiro et al, 2018). As briefly discussed in Section 3, the intra-cluster correlation of our variable of interest -RT C r × Dist r -is very close to zero, which indicates that this clustering is not adequate in our context.…”
Section: Robustnessmentioning
confidence: 91%
“…Table A.2 in Appendix C shows our main results from Tables 3 and 4 with the p-values from our benchmark specification (simple robust standard errors), with clustered standard errors at the meso-region level, and bootstrapped standard errors. Part of the previous literature uses clustered standard errors at the level of aggregation immediately above micro-regions, which in the Brazilian case would correspond to the meso-region (e.g Dix-Carneiro and Kovak, 2015;Dix-Carneiro et al, 2018). As briefly discussed in Section 3, the intra-cluster correlation of our variable of interest -RT C r × Dist r -is very close to zero, which indicates that this clustering is not adequate in our context.…”
Section: Robustnessmentioning
confidence: 91%
“…On the other hand, we use a random sample of all formally employed workers between 2007 and 2013. The administrative panel data set called the Relações Anuais de Informações Sociais (RAIS) is widely used, see Dix‐Carneiro and Kovak (2015). But the restriction to formally employed workers is not innocuous in a developing country like Brazil (Ulyssea, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, researchers have devoted large efforts to assess the value of job skills in different manners. Many surveys and studies have shown evidence of a worldwide positive association between the distributions of job skill mastery and job salary 2 , 3 , 7 , 8 . However, due to the dynamic and indistinct nature of job skill value, traditional market survey-based approaches usually fail to provide a fine-grained and up-to-date analysis.…”
Section: Introductionmentioning
confidence: 99%